Palm olein corrosion inhibitor for aluminium in Hcl solution / Junaidah Jai and Wan Shabuddin Wan Ali - Jai, Junaidah; Wan Ali, Wan Shabuddin (Research Management Institute (RMI), 2011)
Aluminium (Al) is a low cost, lightweight and corrosion resistant material, which corrodes when exposed to pitting agents. Palm olein exhibits characteristics, which indicate its suitability as a corrosion inhibitor. Tween 20, hexane and diethyl triamine were used as additives to Palm olein to form the inhibitor formulation POT20HA. The inhibition efficiency (IE) and behaviour of the POT20HA were determined using potentiodynamic polarization in which Al 6061 samples were immersed in a 1 M HCl solution at 26, 50 and 70 oC in the presence of different POT20HA concentrations: 0, 0.03, 0.07, 0.10, 0.13 and 0.17 M. The IE increased with increasing POT20HA concentration, but decreased with increasing temperature. The work presented indicates that POT20HA is a mixed-type inhibitor capable of inhibiting both corrosive anodic and cathodic reactions. According to the Langmuir isotherm results POT20HA adsorbs on the Al 6061 surface through semiphysiosorption and/or semi-chemisorption. The POT20HA adsorption mechanism on Al 6061 takes through the protonation of micelles by the HCl solution, whereby protonated micelles in the presence of chloride ions adsorb on both cathodic and anodic surface corrosion sites.